2021
DOI: 10.21273/hortsci15507-20
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural Attributes and Root Architectures of Field-grown ‘Valencia’ Trees Grafted on Different Rootstocks Propagated by Seed, Cuttings, and Tissue Culture

Abstract: Huanglongbing (HLB) is a devastating disease of citrus that is found in most citrus production areas around the world. The bacterium associated with HLB resides in and damages the phloem, restricting the movement of photosynthates throughout the plant and leading to tree decline. Considerable root loss can be observed in affected trees even when few disease symptoms are visible aboveground. Root traits can substantially influence tree performance and use of superior rootstocks is one strategy to manage tree he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The largest increase in root length measured with the minirhizotron system occurred from September to October after the transplant of trees into larger pots, and from March to July of the following year, which corresponded to the most active time of leaf and shoot growth. Minirhizotron field studies by Pokhrel et al (2021) found the largest net increase in live root length between June and July after the spring leaf flush. Bevington and Castle (1985) suggested that root growth follows shoot elongation and is stimulated by increases in soil temperature when water is not a limitation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The largest increase in root length measured with the minirhizotron system occurred from September to October after the transplant of trees into larger pots, and from March to July of the following year, which corresponded to the most active time of leaf and shoot growth. Minirhizotron field studies by Pokhrel et al (2021) found the largest net increase in live root length between June and July after the spring leaf flush. Bevington and Castle (1985) suggested that root growth follows shoot elongation and is stimulated by increases in soil temperature when water is not a limitation.…”
Section: Discussionmentioning
confidence: 98%
“…A typical citrus tree root system under present Florida growing conditions is composed mainly of lateral (structural) roots that provide anchorage, and fibrous roots that absorb water and nutrients (Pokhrel et al, 2021). The efficiency of the root system, especially the fibrous roots, can enhance the performance of the tree under disease stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, there was concern about whether the characteristics and health of rootstocks propagated by stem cuttings and tissue culture would be as good as that of rootstocks propagated by seed. But rootstocks propagated by all three methods (seed, cuttings, and tissue culture) have been studied intensively, with clear indication that nursery and field performance are primarily determined by the genetic traits of the rootstock cultivar, and only minimally affected by propagation method (Albrecht et al, 2017(Albrecht et al, , 2020Pokhrel et al, 2021). In one current field trial with Valencia scion and four rootstock clones, a comparison of the rootstocks propagated by nucellar seedlings, stem cuttings, and tissue culture (Figure 1) demonstrated a significant effect of rootstock clone on young tree growth and canopy health, but no significant effect from rootstock propagation type (Table 2).…”
Section: Expanding the Gene Pool By Eliminating Nucellar Embryony As A Required Traitmentioning
confidence: 99%
“…Under this pressure for replanting and resetting HLB-affected groves, there is a clear concern among citrus nursery operators and growers on seed availability of highly demanded rootstocks in Florida. Currently, seed propagation remains the preferred method of rootstock production in commercial citrus nurseries (Albrecht et al, 2020;Pokhrel et al, 2021), in part because there is no evidence on the vertical transmission of viable cells of the HLB pathogen "Candidatus Liberibacter spp." through seeds to citrus seedlings (Belasque Júnior et al, 2009;Bagio et al, 2020), and also because the extended belief that different root architectures arising from vegetative propagation will result in trees of inferior quality as compared to those from seeds (Albrecht et al, 2020); as a result, over 80% of the licensed citrus nurseries prefer uniform liners from seeds rather than from tissue culture sources (Chaires, 2017).…”
Section: Introductionmentioning
confidence: 99%